Development and characterization of thermoset nanocomposites reinforced with cotton fibres recovered from textile waste. Issue 2 (June 2022) - Kamble, Zunjarrao; Behera, Bijoya Kumar; Kimura, Teruo; Haruhiro, Ino
The present research reports thermoset nanocomposites reinforced with cotton fibres extracted from textile waste called as 'shoddy' and graphite oxide nanoparticles as filler. The oriented fibre web of shoddy was produced by using the carding machine and it was used as reinforcement. The thermoset epoxy composites with four different fibre volume fraction values namely 0.1, 0.2, 0.3 and 0.4 were developed. These composites were characterized by mechanical properties to optimize the fibre volume fraction. Further, thermoset epoxy nanocomposites were developed by incorporating graphite oxide nanoparticles as filler in four different weight percentages, namely 0.1, 0.3, 0.5 and 1%. All the composites were characterized for mechanical properties, dynamic mechanical properties, thermal degradation behaviour and water absorption behaviour. It has been found that the developed composites can be used in items of furniture materials and to develop some visible and non-visible automotive components.